A MODEL OF ISLAMIC EDUCATION GUIDANCE ON INHERITED ASSETS INDICATES CONFLICT AMONG HEIRS - MS, Anwar; Pagar, Pagar; Nurasiah, Nurasiah (Sekolah Tinggi Agama Islam Al Hidayah, 2022)
Islamic law has regulated the rules for distributing inheritance to the heirs of the jawil furud in detail and clearly, but the time when it must be carried out and distributed to the heirs is subject to the provisions and provisions of the Syar'i law regarding the time limit that must be carried out so as to maintain the benefit and eliminate harm. The stipulation of a rule governing the timing of Bener Meriah Regent Regulation Number 19 of 2022 has stipulated that 100 days after the death of the heirs must be given the rights of the heirs without any fighting over and controlling each other without the sincerity of the owner of the rights obtained through inheritance. The time-limit provisions can provide benefits to the heirs without any delay in the implementation of the distribution of inheritance. Besides that, the role of Islamic education is to be able to form good character and maintain Islamic values in various aspects of life, including the distribution of inheritance. This refers to the understanding of the legal foundations for the distribution of inherited assets.